APTAMERS AND THEIR APPLICATIONS IN BIOLOGY AND BIOMEDICINE - Imanbekova , M.K.; Stybayeva , G.S.; Revzin , A.; Zholdybaeva , E.V. (Eurasian Journal of Applied Biotechnology, 2017)
Aptamers are synthetic nucleic acids developed to bind specific targets, such as amino acids, drugs, proteins, and other molecules. In nature, aptamers exist as riboswitches, which are genetic regulatory elements. Aptamers can be generated using a method called SELEX, an iterative process of adsorption, separation, and amplification, followed by sequencing of a specific oligonucleotide. The entire SELEX process takes between a week to a month to complete and consists of 8–20 rounds. Aptamers are an excellent alternative to monoclonal antibodies, which are expensive and immunogenic. Advantages that aptamers offer over antibodies include stability, low cost, lack of toxicity and immunogenicity, minimized batch-to-batch variation, and the ability to develop them against a variety of targets. The ease in which aptamers can be synthesised and modified allow for the creation and application of aptamers for use in various fields of biology and medicine, including diagnostics, targeted drug delivery, discovery of new biomarkers, biovisualization, and molecular therapy.